PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER MODEL TUTORIAL INTERAKTIF PADA POKOK BAHASAN RELASI DAN FUNGSI - Yudi Jepri Dianta; Yenita Roza; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThe purpose of this research is to develop a practical computer-based learning media model of an interactive tutorial on the topic of Relation and Fungtion. This study use research and development (R & D) method. Development model used in this study is a model of educational Plomp consists of four stages (phases), namely: (1) the initial research, (2) design, (3) the realization phase, (4) the testing evaluation and review phase. The data analysis technique that is used is the quantitative descriptive analysis. Based on the results of the data analysis and discussion, it can be concluded that the model of computer-based instructional interactive tutorial has praktical. Because these media is very valid, considered to be experts with an average value of 3.54 and this media have a very good assessment result from the achievement and response quetioner with the average rating score 92.19%.Key words: Computer-Based Learning Media, Interactive Tutorial, Research And Development (R&D), Practical,